2021
DOI: 10.1021/acschemneuro.1c00355
|View full text |Cite
|
Sign up to set email alerts
|

Role of the English (H6R) Mutation on the Structural Properties of Aβ40 and Aβ42 Owing to the Histidine Tautomeric Effect

Abstract: As an intrinsic origin cause, histidine behaviors play a critical role in protein misfolding processes. Generally, the English (H6R) mutation will disrupt H6 interactions. However, the structural properties of Aβ40 H6R and Aβ42 H6R under the complex influence of a histidine tautomeric effect and an H6R mutation remain unclear. Therefore, we performed a replica exchange molecular dynamics simulation to unveil such structural properties. Our result showed that the H6R substitute could promote the generation of β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…36 The different states of histidine play a crucial role in the structure and aggregation properties of the Aβ aggregation process. 43,44 Compared to the conformational shift from helix to coil in deprotonated Aβ(1−40), protonation of histidine in Aβ (1− 42) stimulates interactions between the N-and C-terminus, leading to an increase in β-sheet content and rapid aggregation in an acidic environment. 45 Furthermore, previous studies of the middle chain substitution with different tautomeric and/or protonated states in Aβ mature fibrils have demonstrated that histidines directly contribute to the β-strand structure and influence the N-terminus H-bonding interaction networks, 38,46,47 However, the impact of histidine protonation behavior on the edge chain of Aβ mature fibrils remains unclear and requires further investigation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 The different states of histidine play a crucial role in the structure and aggregation properties of the Aβ aggregation process. 43,44 Compared to the conformational shift from helix to coil in deprotonated Aβ(1−40), protonation of histidine in Aβ (1− 42) stimulates interactions between the N-and C-terminus, leading to an increase in β-sheet content and rapid aggregation in an acidic environment. 45 Furthermore, previous studies of the middle chain substitution with different tautomeric and/or protonated states in Aβ mature fibrils have demonstrated that histidines directly contribute to the β-strand structure and influence the N-terminus H-bonding interaction networks, 38,46,47 However, the impact of histidine protonation behavior on the edge chain of Aβ mature fibrils remains unclear and requires further investigation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Histidine is an essential amino acid that exhibits certain effects on structural properties and aggregation properties. The histidine behaviors include tautomerization behavior and protonation behavior as the imidazole group of histidine readily donates and accepts protons, resulting in three states for histidine, as shown in Figure a: the tautomerization states (the ε state (Nε-H) (HIE) and the δ state (Nδ-H) (HID)) and the protonation state (the (p) state (HIP), both Nε-H and Nδ-H). , The ε:δ ratio of histidine is approximately 1:0.16 in the gas phase, but this ratio can be influenced by various external factors, including pH, side chain imidazole ring, and the N atom orientation and protein amino acid position . The different states of histidine play a crucial role in the structure and aggregation properties of the Aβ aggregation process. , Compared to the conformational shift from helix to coil in deprotonated Aβ(1–40), protonation of histidine in Aβ(1–42) stimulates interactions between the N- and C-terminus, leading to an increase in β-sheet content and rapid aggregation in an acidic environment . Furthermore, previous studies of the middle chain substitution with different tautomeric and/or protonated states in Aβ mature fibrils have demonstrated that histidines directly contribute to the β-strand structure and influence the N-terminus H-bonding interaction networks, ,, However, the impact of histidine protonation behavior on the edge chain of Aβ mature fibrils remains unclear and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Our earlier research has shown that each histidine's e, d, or p state has a unique impact on the structure of Ab fragments. 64,[70][71][72][73] Furthermore, under conditions of protonated and deprotonated norepinephrine, the various processes of degradation on Ab(1-42) protofibrils were discovered. 74 Additionally, the redox activity in the metal-Ab complex 75 can be modulated by the status of the histidine residues.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, a novel histidine tautomerism/protonation hypothesis accounting for the pathogenesis of AD and other neurological diseases has been suggested by our research team. 11–26 We have demonstrated that different protonated states in the histidine imidazole ring are related to the conformational characteristics of diverse misfolded peptides (namely Aβ, tau, amylin, and prion) and can influence fibrillization processes in polypeptides, resulting in proteopathies. This histidine hypothesis implies that protein accumulation may occur inherently rather than as a consequence of extrinsic agents.…”
Section: Introductionmentioning
confidence: 99%